Effect of bacteriophage P1 lysogeny on lipopolysaccharide composition and the lambda receptor of Escherichia coli. - Tomás, J M (1984)
The outer membrane of Escherichia coli was altered as a consequence of lysogeny by bacteriophages P1 and P1 cmts. The predominant change was a reduction in the size of lipopolysaccharide to a heptose-deficient form. P1 cmts lysogens were still sensitive to several bacteriophages but were resistant to lambda vir. Neither whole cells nor solubilized outer membranes from P1 cmts lysogens were able to inactivate lambda vir, and 32P-labeled lambda vir was unable to adsorb to P1 cmts lysogens. P1 cmts lysogens were also affected in maltose transport. The level of periplasmic maltose-binding protein was reduced somewhat, but there was no significant reduction in the level of the outer membrane lambda receptor (LamB). These membrane abnormalities were all corrected in strains cured of P1 cmts. It is suggested that P1 cmts affects lipopolysaccharide biosynthesis by a phage conversion mechanism and consequently the function of the lambda receptor.